Consuming Sumo Wrestlers: Taste, Commensality, and Authenticity in Japanese Food. (1st October 2016) - Tierney, R. Kenji
Abstract : Chanko stew—making, serving, and eating it—is at the core of Japanese sumo wrestlers' social and professional lives. Sumo wrestlers are chanko stew. It is a critical means to make social connections with the outside world by inviting important guests to share their food. Eating with wrestlers is the authentic "sumo experience." Chanko is also consumed outside of the wrestlers' training houses in a myriad of ways. Ranging from a luxurious seafood dish served in restaurants to cheap sumo-flavored instant ramen sold in convenience stores, each incarnation claims to be authentic. Although disparate and overlapping, producers use two main strategies to assert authenticity. While the first strategy—taste—focuses on the flavor or ingredients of the dish itself, the second—commensality—emphasizes social ties to make claims of authenticity. Recognizing the difference between these two helps to explain how authenticity works in Japan. By examining chanko stew as an "authentic" cultural practice within, bridging, and outside of the "sumo world, " we can learn how authenticity itself takes on a variety of forms and is used to make connections, cultural meaning and profits.